Genomic Profiling of Peripheral T-Cell Lymphoma, Unspecified, and Anaplastic Large T-Cell Lymphoma Delineates Novel Recurrent Chromosomal Alterations - Zettl, Andreas (American Society for Investigative Pathology, 2004)
To characterize genetic alterations in peripheral T-cell lymphoma, not otherwise specified (PTCL NOS), and anaplastic large T-cell lymphoma (ALCL), 42 PTCL NOS and 37 ALCL [17 anaplastic large cell kinase (ALK)-negative ALCL, 9 ALK-positive ALCL, 11 cutaneous ALCL] were analyzed by comparative genomic hybridization. Among 36 de novo PTCL NOS, recurrent chromosomal losses were found on chromosomes 13q (minimally overlapping region 13q21, 36% of cases), 6q and 9p (6q21 and 9p21-pter, in 31% of cases each), 10q and 12q (10q23-24 and 12q21-q22, in 28% of cases each), and 5q (5q21, 25% of cases). Recurrent gains were found on chromosome 7q22-qter (31% of cases). In 11 PTCL NOS, high-level amplifications were observed, among them 3 cases with amplification of 12p13 that was restricted to cytotoxic PTCL NOS. Whereas cutaneous ALCL and ALK-positive ALCL showed few recurrent chromosomal imbalances, ALK-negative ALCL displayed recurrent chromosomal gains of 1q (1q41-qter, 46%), and losses of 6q (6q21, 31%) and 13q (13q21-q22, 23%). Losses of chromosomes 5q, 10q, and 12q characterized a group of noncytotoxic nodal CD5+ peripheral T-cell lymphomas. The genetics of PTCL NOS and ALK-negative ALCL differ from other T-NHLs characterized genetically so far, among them enteropathy-type T-cell lymphoma, T-cell prolymphocytic leukemia, and adult T-cell lymphoma/leukemia.